Tax Audit Between Revenue Target (Budgeter) and Law Enforcement (Law Inforcement) in the Context of Securing State Revenue - Teng Sauh Hwee; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
In theory, a tax audit is a way (means) to identify discrepancies between commercial and tax reports and errors in the application of tax regulations by taxpayers. Tax audit is part of tax administration whose job is to determine the extent of formal and substantive compliance by taxpayers. The main problem of this audit is how the tax audit is carried out at the Tangerang Tax Audit and Investigation Office and whether the tax audit fulfills two objectives, namely achieving sales targets and law enforcement, as well as how the overall audit results can be followed up. within the framework of a future audit and investigative function. The research methodology used in compiling this work is a descriptive analysis method using data collection techniques in the form of literature reviews and field studies, as well as in-depth interviews with relevant parties